Prove this immidiately
in Trigonometry Answers by (120 points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

We will take RHS and prove LHS, so it is given that, cosx+cosy+cosz=0......(1)sinx+siny+sinz=0.......(2)Now multiplying equation 1 by cosy , cos z, cosx one by one we will get threeequation as, cosycosx+ cos 2 y+coszcosy=0......(3) cosxcosz+cosycosz+ cos 2 z=0......(4) cos 2 x+cosycosx+coszcosx=0......(5) ANd now multiply equation 2 by sinx, siny , sinz then we will get three equation as, sin 2 x+sinysinx+sinzsinx=0.......(6) sinxsiny+ sin 2 y+sinzsiny=0.......(7) sinxsinz+sinysinz+ sin 2 z=0.......(8) Add all the six equation we get,2cosxcosy+2sinxsiny+2cosycosz+2sinysinz+2coszcosx+2sinzsinx+ + sin 2 x+ cos 2 x+ cos 2 y+ sin 2 y+ sin 2 z + cos 2 z=0 2cos(x−y)+2cos(y−z)+2cos(z−x)+3=02cos(x−y)+2cos(y−z)+2cos(z−x)=−3cos(x−y)+cos(y−z)+cos(z−x)=− 3 2 =LHS
by

Related questions

1 answer
1 answer
asked May 31, 2013 in Trigonometry Answers by anonymous | 157 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
81,951 questions
86,346 answers
2,238 comments
71,628 users